Consumer Protection law - egypt (2025)
Law no. 181 of the year 2018: promulgating the Consumer Protection law – part 1: definition – part 2: obligations of the supplier and advertiser – part 3: consumer Protection agency – part 4: non-governmental organizations concerned with consumer Protection – part 5: penalties قانون رقم 181 لسنة 2018 بإصدار قانون حماية المستهلك – الباب الأول التعريفات – الباب الثانى التزامات المورد والمعلن – الباب الثالث جهاز حماية المستهلك – الباب الرابع الجمعيات الأهلية المعنية بحماية المستهلك – الباب الخامس العقوبات